2019
DOI: 10.4102/aej.v7i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation2 – Evaluating the national evaluation system in South Africa: What has been achieved in the first 5 years?

Abstract: Background: South Africa has pioneered national evaluation systems (NESs) along with Canada, Mexico, Colombia, Chile, Uganda and Benin. South Africa’s National Evaluation Policy Framework (NEPF) was approved by Cabinet in November 2011. An evaluation of the NES started in September 2016.Objectives: The purpose of the evaluation was to assess whether the NES had had an impact on the programmes and policies evaluated, the departments involved and other key stakeholders; and to determine how the system needs to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…They sought to determine the extent to which evaluations were used in policymaking. Second, Goldman and et al (2019) assessed the South African evaluation system and its impacts on the programs and policies evaluated, the departments involved and other key stakeholders. In both cases, the methodology employed was based on a theory-based approach that included multiple lines of inquiry.…”
Section: Government-wide Assessments Of Evaluation Functionsmentioning
confidence: 99%
“…They sought to determine the extent to which evaluations were used in policymaking. Second, Goldman and et al (2019) assessed the South African evaluation system and its impacts on the programs and policies evaluated, the departments involved and other key stakeholders. In both cases, the methodology employed was based on a theory-based approach that included multiple lines of inquiry.…”
Section: Government-wide Assessments Of Evaluation Functionsmentioning
confidence: 99%
“…The last annual report undertaken on the NES was for the period 2016/17 (DPME, 2017), and it summarised the situation at that time, as does the evaluation of the NES conducted in 2016/2017. The report indicated that while many elements were working, the improvement plan system needed to be followed up and tracked more rigorously (Goldman et al, 2019).…”
Section: Links Of the Nes To The South African Parliamentary Systemmentioning
confidence: 99%
“…In addition, while it is difficult to assess use of evaluations, case studies revealed that instrumental and process use were prominent. It has been argued that there is a high return on evaluations of between R7 and R13 per rand invested (Goldman et al, 2019).…”
Section: Lessonsmentioning
confidence: 99%
“…As discussed in Goldman et al (2019), the evaluation made use of a theory-based approach including international benchmarking; five national and four provincial case studies; 112 key informant interviews; a survey with 86 responses; and a cost-benefit analysis of a sample of evaluations. From 2011 to the end of December 2016, 67 national evaluations were…”
Section: Strengthening the Provincial Evaluation System Using The Findings From The Evaluation Of The National Evaluation Systemmentioning
confidence: 99%